Knowledge of the patients in treatment of hemodialise about arteriovenous fistula - Furtado, Angelina Monteiro (2006)
We sought to verify the knowledge of the patients who are going through haemodialysis concerning their arterovenous fistula (AVF). This is a descriptive study which was accomplished at a haemodialysis clinic in the city of Fortaleza-CE. We selected, at random, 21 patients going through haemodialysis treatment. Concerning the results, we obtained the following data: 11 women and 10 men aged between 30 and 50 years, predominantly single, familiar income varying between 2 and 4 minimum wages, most of them have not graduated in high school and are retired. As far as knowledge is concerned, most of them declared not to know about the anatomo-physiology and durability of their fistula and were not aware of the amount of fistulas which can be formed. However we got to the conclusion that there is a great deficit of knowledge on the part of the interviewed with regard to his fistula. We agree that it is up to the professionals who assist such patients to supply them with clear, concrete and objective information about the issue once it is really important to the patients to learn about their problems.